Identification threats to the state information security in the text content of social networking services - Барабаш, О. В.; Грищук, Р. В.; Молодецька-Гринчук, К. В. (Science-based technologies, 2018)
Social networking services are one of the most popular mass media society through effective tool to meet the information and communication needs of users, called actors. Social networking services are used by leading countries of the world as an effective tool for information operations. The development of effective approaches to detecting threats in the content of social networking services is an important scientific and applied task on the way of ensuring information security of man, society, and the state. The paper proposes a conceptual basis for the study of information influence on actors in the text content of social networking services. It is established that the basis of the conceptual model consists the types, stages and components of information influence on actors. On the basis of the proposed conceptual model, a system model for detecting threats to state information security in the text content of social networking services has been developed. Determined its main components and specified the features of their interaction with each other. The system model was used in developing an approach to detecting threats in the text content based on the integration of semantic and latent semantic analysis. The proposed approach differs from the known use of the weighted components of the semantic kernel in order to increase the relevance of the selected text content. Ranking of selected text publications according to their search query allows to increase the efficiency of threats detection to state information security on the ontologies. Addition of a multiplicity of threats templates is carried out with the involvement of experts in information security of the state. The proposed approach to detecting threats in the text content of virtual communities can improve the efficiency of the state information security system in social networking services.